THE ANOMALY OF CONTEMPT IN THE FACE OF THE COURT RECORD (UUM Journal of Legal Studies, 2011)
Categories and forms of contempt of court are not closed, whereby, judges have the discretion to use this power when they deem appropriate. However, there are a number of traditional categories that have been created and used by the courts in Malaysia and the United Kingdom. Contempt in the face of the court record has not been a traditional category of contempt in either country, and, thus far, has only been recognised in Malaysia in one case. The aims of this paper are to consider what the scope of contempt in the face of the court record is, when it should apply and whether this category is clearly distinct from the other existing categories of contempt of court. It is suggested that it may not have been necessary to create the category of contempt in the face of the court record as there appears to be an overlap between this category and the other categories of contempt of court.Keywords: contempt of court, contempt in the face of the court record.